(untitled) (Journal of Educational Sciences, 2023)
The study of problems of teaching a foreign language does not lose its relevance among Kazakhstan researchers in connection with the pace of development of the modern labor market. The need to participate in international scientific conferences, to study and analyze the results of scientific research presented in foreign sources, to communicate and exchange experiences with foreign colleagues have become part of today’s reality for the professional development of specialists in all areas of human activity. Representatives of all kinds of specializations face these professionally significant situations, where the use of a foreign language is a self-evident condition for achieving profession-related goals and meeting professional needs. In this regard, this paper examines the problem of teaching a foreign language for professional purposes to students of non-linguistic universities in Kazakhstan. In this study, general theoretical methods of research were applied: analysis, synthesis, generalization. In the course of this research, the following results were achieved: (а) theoretical review and analysis of professional foreign language training models proposed by Kazakhstani researchers for technical, financial and economic, agroeconomic profiles were carried out; (b) the principles that most closely determine the success of the process of teaching a foreign language for professional purposes have been identified and systematized; (c) a basic set of tasks and exercises to improve the effectiveness of the process of learning a foreign language for professional purposes was proposed based on the synthesis of the experience of domestic researchers. Key words: foreign language education, foreign language teaching, English for professional purposes, professional communication.